Modified step-cut osteotomy for correction of post-traumatic cubitus varus deformity: a report of 19 cases. Issue 5 (September 2016) - Takagi, Takehiko; Seki, Atsuhito; Takayama, Shinichiro; Watanabe, Masahiko; Mochida, Joji
Abstract : We reviewed the outcomes of post-traumatic varus deformity treated with modified step-cut osteotomy in 19 patients (average age, 7.4 years; range, 4.3–16.8 years at time of surgery). The average follow-up period was 29.6 months. The mean range of motion was 15.0°/124.7° (extension/flexion) before surgery and 6.8°/132.6° at final follow-up. The humerus–elbow–wrist angle was −21.1° before surgery and 4.2° at final follow-up, with a loss of 4.4° from the value of the humerus–elbow–wrist angle after the surgery. Osteotomy was fixed with Kirschner wires, and, in five cases, chips of excised bone could be inserted to avoid elbow extension. However, in eight cases, usually concerning younger patients, the elbow was fixed in hyperextension higher than 5°. No patient developed postoperative infections or later complications. Only one patient had transient nerve palsy. The modified step-cut osteotomy can precisely and stably correct the varus deformity in the coronal plane, especially in patients under 10 years of age. To avoid radial nerve palsy, we recommend that the retractors be removed sometimes during the operation.